Embracing the Beyond Budgeting Method to Enhance Performance in the Surakarta City Government - Sugiarti; Zulfikar; Triyono (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aims to explore the application of the Beyond Budgeting method as a strategic approach to enhance performance within the Surakarta City Government. Through observational methods and SWOT analysis, the strengths, weaknesses, opportunities, and threats facing the local government were identified. The findings reveal a pressing need for innovative management strategies, particularly in addressing issues such as corruption prevention, financial deficits, and the efficient allocation of resources. Embracing the Beyond Budgeting method emerges as a novel solution to streamline operations, foster transparency, and promote accountability. This research underscores the importance of adaptive governance models in navigating complex challenges faced by municipal administrations. The implications of adopting the Beyond Budgeting method include improved decision-making processes, enhanced service delivery, and sustainable development outcomes.